Analysis of Graffiti in State University of Malang, East Java, Indonesia. - Jupri, Jupri (Jurnal Ilmiah Mandala Education (JIME), 2022)
The art of graffiti in general is adequately devoted in the environment or compound of myriads of universities (mostly undergraduate) in Indonesia. The objectives of showing/painting/brushing graffiti by undergraduate students in Indonesian universities are varied pursuant to the intended body of literature that the students (the writers/the makers) are willing to show off. This research investigated the categories, classification, information of graffiti that the researcher found in State University of Malang (UM), East Java, Indonesia. The researcher applied ethnography research in observing and/or interacting with the research participants in their real-life environment. This research was focused on analyzing the graffiti found in the area of State University of Malang. The researcher took ten participants from the students of undergraduate program, State University of Malang which is located in Jl. Semarang No.5, Sumbersari, Kec. Lowokwaru, Kota Malang, Jawa Timur, Indonesia. Interview and observation were utilized in collecting the data. The researcher found that the graffiti in the surrounding of State University of Malang (UM) are categorized into: tags graffiti, latrinalia graffiti, humorous graffiti, declarative graffiti, and conversational graffiti. The researcher cannot categorize them into public graffiti because they are not written on public spaces and sites; they are only addressed for undergraduate students in State University of Malang (UM). They are also not classified into historical graffiti because the researcher had direct access to the writers of the graffiti. They don’t belong to folk epigraphy graffito because they do not provide/describe any inscriptions drawn inside the graffito. The researcher also found that the men in charge seem to be no problem for them and likely to allow these groups of students to be creative in releasing their ego through graffiti. Finally, the students who designed and wrote the graffiti belonged to certain number of groups who tend to have apparently ‘lower point’ or GPA (grade point average) in the campus community. They sub-divide themselves, verbally speak and write with certain genre and these graffiti are likely to be their specification. They are busy of taking care of their domain of organization and any other kinds of UKM. They tend to separate their groups among others so they appear to be different section (genre) of college community.